Accuracy of the Australian National Death Index: comparison with adjudicated fatal outcomes among Australian participants in the Long‐term Intervention with Pravastatin in Ischaemic Disease (LIPID) study - Dianna Magliano; Danny Liew; Helen Pater; Adrienne Kirby; David Hunt; John Simes; Vijaya Sundararajan; Andrew Tonkin (Elsevier, 2003)
Abstract Objective: To assess the accuracy of the Australian National Death Index (NDI) in identifying deaths and recording cardiovascular and cancer causes of death. Methods: Adjudicated mortality data from Australian participants in the Long‐term Intervention with Pravastatin in Ischaemic Disease (LIPID) study up until September 1999 were used as reference. Nine hundred and eighty deceased subjects and 4,841 surviving subjects were matched to the NDI by name, date of birth, date of death and postcode. Matching rigour was confirmed by manual review. Deaths ascribed to cardiovascular and cancer causes within the NDI were also compared against LIPID‐adjudicated causes. Results: The NDI displayed 93.7% sensitivity and 100% specificity for the identification of deaths. Mis‐recording of identifiers was responsible for 69% of known deaths not matching to the NDI and, if eliminated, would have increased the sensitivity to 98.0%. Among deceased subjects who matched to the NDI, cause of death was recorded in 96.2%. The sensitivity and specificity for cardiovascular deaths were 92.5% and 89.6%, respectively, and for cancer deaths 95.2% and 99.2%, respectively. Conclusion: Much of the inaccuracy of the NDI could potentially be overcome by the use of unique identifiers. Among deaths identified by the NDI, those due to cardiovascular disease are more likely to be inaccurately recorded than cancer‐related deaths, probably because less uncertainty surrounds the presence or absence of terminal malignant disease.